Pattern of Defence Injuries in Homicidal Deaths - R, Dayananda; Kumar, M P; Rayamane, Anand P; Saraf, Ashish; Rav, N; Chandrashekar, T N (Journal of Indian Academy of Forensic Medicine, 2015)
Defence wounds are injuries which are suffered by an individual in an attempt to save oneself  from assault or while defending oneself from the offenders. Based on the presence of such injuries it can  be opined that the victim was conscious, could comprehend the attack and provided resistance during the  assault. The type of injury sustained also gives an idea regarding the weapon of offence. This study is a  retrospective study conducted at Mysore Medical College & Research Institute, Mysore. The study was  conducted for a period of five years 2008 – 2013. Of the total 216 cases of homicide during this period 88  cases had defence injuries. Males outnumbered females in presence of defence injuries. Sharp weapon  was used in 64.8% cases where as blunt weapon in 21.6% cases. The probability that defence injuries  can be seen is rising with the number of wounds. Forearm was the commonest site of defence injuries.
Keywords: Defence wound; Injuries; Assault; Weapon of Offence